Neuroprotective effect of anodal transcranial direct current stimulation on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced neurotoxicity in mice through modulating mitochondrial dynamics - Lee, Sang-Bin; Youn, Jinyoung; Jang, Wooyoung; Yang, Hyun Ok (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the accumulation of protein inclusions and the loss of dopaminergic neurons. Abnormal mitochondrial homeostasis is thought to be important for the pathogenesis of PD. Transcranial direct current stimulation (tDCS), a noninvasive brain stimulation technique, constitutes a promising approach for promoting recovery of various neurological conditions. However, little is known about its mechanism of action. The present study elucidated the neuroprotective effects of tDCS on the mitochondrial quality control pathway in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mouse model. We used the MPTP-induced neurotoxicity in vivo model. Mice were stimulated for 5 consecutive days with MPTP treatment. After observation of behavioral alteration using the rotarod test, mice were sacrificed for the measurement of the PD- and mitochondrial quality control-related protein levels in the substantia nigra. tDCS improved the behavioral alterations and changes in tyrosine hydroxylase levels in MPTP-treated mice. Furthermore, tDCS attenuated mitochondrial damage, as indicated by diminished mitochondrial swelling and mitochondrial glutamate dehydrogenase activity in the MPTP-induced PD mouse model. MPTP significantly increased mitophagy and decreased mitochondrial biogenesis-related proteins. These changes were attenuated by tDCS. Furthermore, MPTP significantly increased fission-related protein dynamin-related protein 1 with no effect on fusion-related protein mitofusin-2, and tDCS attenuated these changes. Our findings demonstrated the neuroprotective effect of anodal tDCS on the MPTP-induced neurotoxic mouse model through suppressing excessive mitophagy and balancing mitochondrial dynamics. The neuroprotective effect of anodal tDCS with modulation of mitochondrial dynamics provides a new therapeutic strategy for the treatment of PD.
Keywords: PARKINSONS-DISEASE; MITOPHAGY; INHIBITION; ACTIVATION; NEURONS; DEATH